A Meta-synthesis in Gender Mainstreaming and Promoting Gender-Responsive Teaching and School Culture in Basic Education - Marlon F Adlit; Darren Rey C Javier; John Cyrus L Doblada (IKAT: The Indonesian Journal of Southeast Asian Studies, 2026)
Gender mainstreaming has been institutionalized in Philippine basic education through the Gender and Development (GAD) framework to promote equity, inclusion, and gender-responsive learning environments. Despite extensive policy support, empirical studies indicate uneven implementation and impact across schools. This study employed a qualitative meta-synthesis to integrate and interpret findings from 43 empirical and conceptual studies on gender mainstreaming in Philippine basic education. Guided by interpretive, integrative, and critical-reflexive approaches, the meta-synthesis examined teachers’ awareness and understanding of gender mainstreaming, the extent of gender-responsive teaching practices, manifestations of gender mainstreaming in school culture, implementation challenges, and the relationships between gender mainstreaming and gender-responsive outcomes. The findings reveal that teachers generally demonstrate moderate to high awareness of GAD policies; however, this awareness is largely procedural and does not consistently translate into transformative pedagogical practices. Gender-responsive teaching is often limited to surface-level strategies, while school culture reflects strong formal compliance but weaker integration into everyday practices. Persistent challenges include limited professional development, weak monitoring mechanisms, leadership constraints, and sociocultural resistance, particularly regarding gender diversity and LGBTQ+ inclusion. Nevertheless, a positive relationship emerges between the depth of gender mainstreaming and the promotion of inclusive teaching practices and supportive school cultures, especially when supported by strong leadership and sustained capacity-building. The study concludes that advancing gender mainstreaming in basic education requires moving beyond compliance-oriented implementation toward transformative integration across pedagogy, leadership, and organizational culture.